Finding faithful elders and deacons - Anyabwile, Thabiti M., 1970- (Wheaton, Ill. : Crossway, 2012)
Every church leader knows the qualifications for elders and deacons that are spelled out in the Bible, but actually finding other leaders who fulfill the biblical qualifications can be difficult. Thabiti Anyabwile writes from his expertise as a pastor and elder, showing how to identify and reproduce legitimate leaders and willing servants throughout the ranks of the local church. Balancing thoughtful analysis of pertinent passages with thorough application for practical use in a contemporary context, Anyabwile answers the questions, "Who should we look for to lead and serve in the church?" and "What should they do to fulfill their calling?" --from publisher description
Choosing your waiter : an introduction to deacons -- Full of the spirit and wisdom -- Sincere -- Sober and content -- Keeps hold of the faith -- Tried and true -- Sheep and shepherds : an introduction to elders -- Desires a noble task -- Above reproach -- A one-woman man -- Sober-minded, self-controlled, respectable -- Hospitable -- Able to teach -- Sober, gentle, peacemaking -- Not a lover of money -- Leader at home -- Mature and humble -- Respected by outsiders -- Elders refute error -- Elders avoid myths and train for godliness -- Elders hope in God -- Elders command -- Elders let no one despise their youth -- Elders set an example -- Elders teach -- Elders grow -- Elders watch their life -- Elders watch their doctrine.
Includes bibliographical references (p. 165-166) and indexes.
Keywords: Elders (Church officers) -- Baptists; Deacons -- Baptists